Extent and Factors Associated with Adherence to Antidepressant Treatment During Acute and Continuation Phase Depression Treatment Among Older Adults with Dementia and Major Depressive Disorder - Bhattacharjee S (Dove Medical Press, 2020)
Sandipan Bhattacharjee,1 Jeannie K Lee,1 Nina Vadiei,1 Asad E Patanwala,2 Daniel C Malone,3 Shannon M Knapp,4 Wei-Hsuan Lo-Ciganic,5 William J Burke6 1Department of Pharmacy Practice and Science, College of Pharmacy, The University of Arizona, Tucson, AZ, USA; 2Sydney Pharmacy School, University of Sydney, Sydney, Australia; 3Department of Pharmacotherapy, Skaggs College of Pharmacy, University of Utah, Salt Lake City, UT, USA; 4Statistics Consulting Laboratory, Bio5 Institute, The University of Arizona, Tucson, AZ, USA; 5Department of Pharmaceutical Outcomes & Policy, College of Pharmacy, University of Florida, Gainesville, FL, USA; 6Banner Alzheimer’s Institute, Phoenix, AZ, USACorrespondence: Sandipan BhattacharjeeDepartment of Pharmacy Practice and Science, The University of Arizona College of Pharmacy, Tucson, AZ, USATel +1 520 626-4124Fax +1 520-626-7355Email bhattacharjee@pharmacy.arizona.eduPurpose: Little is known about adherence to antidepressant treatment during acute and continuation phase of depression among older adults with dementia and newly diagnosed major depressive disorders (MDD). This study estimated the extent of and factors associated with adherence to acute and continuation phase antidepressant treatment among older adults with dementia and newly diagnosed MDD.Methods: We conducted a retrospective cohort study using the Medicare 5% sample claims data (2012– 2013) among older adults (age≥ 65 years) with dementia who were newly diagnosed with MDD. Intake period of our study was from 01-May-2012 through 30-April-2013. The dependent variables of this study were acute and continuation phase depression treatment adherence. Factors associated with acute and continuation phase antidepressant treatment adherence were identified using multiple logistic regression analyses.Results: The final study sample consisted of 6239 [adherent: N=4644 (74.44%)] and 5617 [adherent: N=3584 (63.81%)] older adults with dementia and MDD during the acute and continuation phase treatment, respectively. During the acute phase, only race/ethnicity was significantly associated with adherence to depression treatment, whereas race/ethnicity and baseline antipsychotic use were significantly associated with adherence to depression treatment during the continuation phase.Conclusion: Approximately, 74% and 64% older adults with dementia and MDD were adherent to acute and continuation phase antidepressant treatment in this nationally representative sample of Medicare beneficiaries, and we identified several modifiable and non-modifiable factors associated with adherence.Keywords: dementia, depression, antidepressants, adherence, acute phase depression, continuation phase depression